PHP 8 Solutions: Dynamic Web Design and Development Made Easy, 5th Edition - Powers, David (Apress, 2021)
This book doesn't just provide a collection of ready-made scripts: each PHP solution builds on what's gone before, teaching you the basics of PHP and database design quickly and painlessly. Youll learn how to optimize your code using object-oriented programming (OOP) techniques. --